Investigation of deposit effect on multi-hole injector spray characteristics and air/fuel mixing process. (1st March 2017) - Wang, Bo; Badawy, Tawfik; Jiang, Yizhou; Xu, Hongming; Ghafourian, Akbar; Zhang, Xinyu
Highlights: Effects of injector deposit on spray and air/fuel mixing process were investigated. Injector deposit altered the designed spray structure and droplet behaviours. Injector deposit led to severe fuel impingement in the late injection cases. Over rich zones found for the coked injector can lead to higher emissions. Abstract: An optical-based experimental study of the injector deposit effect on a multi-hole GDI injector was performed first. After carefully calibrating the spray model with the experiment data, a three-dimensional computational fluid dynamics (CFD) simulation was then carried out to study the deposit effect on the air/fuel mixture preparation process in an optical research GDI engine. Six different injection timings were used for full-cycle simulations. The numerical engine condition was at stoichiometric ratio, 1200 rpm and 150 bar injection pressure. The experimental results showed that injector deposit would lead to lower fuel mass flow rate, with 5.4%, 5.7% and 6.1% loss at 50, 100 and 150 bar respectively. Injector deposit resulted in longer penetration length and the effect displayed hole to hole difference. The maximum increment was observed for the ignition jets with 11.6% at 150 bar. Injector deposit led to higher droplet velocity and larger droplet size and the difference increased with injection pressure. For the air/fuel mixing simulation, the injector deposit led to more fuel impingement on the piston and cylinder walls, as well as a lower mean equivalence ratio during late injection events. The distorted spray pattern led to higher fuel stratification level. In very late injection cases, the injector deposit led to a very lean mixture near the spark plug which could result in unstable engine performance; while the rich regions at the cylinder sides could result in higher emissions. Comparison of computed results with PLIF (planar laser induced fluorescence) images provided a satisfactory validation for the model.